A field and video annotation guide for baited remote underwater stereo‐video surveys of demersal fish assemblages. Issue 11 (24th September 2020) - Langlois, Tim; Goetze, Jordan; Bond, Todd; Monk, Jacquomo; Abesamis, Rene A.; Asher, Jacob; Barrett, Neville; Bernard, Anthony T. F.; Bouchet, Phil J.; Birt, Matthew J.; Cappo, Mike; Currey‐Randall, Leanne M.; et al.
Abstract: Baited remote underwater stereo‐video systems (stereo‐BRUVs) are a popular tool to sample demersal fish assemblages and gather data on their relative abundance and body size structure in a robust, cost‐effective and non‐invasive manner. Given the rapid uptake of the method, subtle differences have emerged in the way stereo‐BRUVs are deployed and how the resulting imagery is annotated. These disparities limit the interoperability of datasets obtained across studies, preventing broadscale insights into the dynamics of ecological systems. We provide the first globally accepted guide for using stereo‐BRUVs to survey demersal fish assemblages and associated benthic habitats. Information on stereo‐BRUVs design, camera settings, field operations and image annotation are outlined. Additionally, we provide links to protocols for data validation, archiving and sharing. Globally, the use of stereo‐BRUVs is spreading rapidly. We provide a standardized protocol that will reduce methodological variation among researchers and encourage the use of Findable, Accessible, Interoperable and Reusable workflows to increase the ability to synthesize global datasets and answer a broad suite of ecological questions.